Mapping molecular recognition of β1,3-1,4-glucans by a surface glycan-binding protein from the human gut symbiont Bacteroides ovatus - Correia,VG; Trovao,F; Pinheiro,BA; Bras,JLA; Silva,LM; Nunes,C; Coimbra,MA; Liu,Y; Feizi,T; Fontes,CMGA; Mulloy,B; Chai,W; et al. (Microbiology Spectrum, 2021)
A multigene polysaccharide utilization locus (PUL) encoding enzymes and surface carbohydrate (glycan)-binding proteins (SGBPs) was recently identified in prominent members of Bacteroidetes in the human gut and characterized in Bacteroides ovatus. This PUL-encoded system specifically targets mixed-linkage β1,3-1,4-glucans, a group of diet-derived carbohydrates that promote a healthy microbiota and have potential as prebiotics. The BoSGBPMLG-A protein encoded by the BACOVA_2743 gene is a SusD-like protein that plays a key role in the PUL’s specificity and functionality. Here, we perform a detailed analysis of the molecular determinants underlying carbohydrate binding by BoSGBPMLG-A, combining carbohydrate microarray technology with quantitative affinity studies and a high-resolution X-ray crystallography structure of the complex of BoSGBPMLG-A with a β1,3-1,4-nonasaccharide. We demonstrate its unique binding specificity toward β1,3-1,4-gluco-oligosaccharides, with increasing binding affinities up to the octasaccharide and dependency on the number and position of β1,3 linkages. The interaction is defined by a 41-Å-long extended binding site that accommodates the oligosaccharide in a mode distinct from that of previously described bacterial β1,3-1,4-glucan-binding proteins. In addition to the shape complementarity mediated by CH-π interactions, a complex hydrogen bonding network complemented by a high number of key ordered water molecules establishes additional specific interactions with the oligosaccharide. These support the twisted conformation of the β-glucan backbone imposed by the β1,3 linkages and explain the dependency on the oligosaccharide chain length. We propose that the specificity of the PUL conferred by BoSGBPMLG-A to import long β1,3-1,4-glucan oligosaccharides to the bacterial periplasm allows Bacteroidetes to outcompete bacteria that lack this PUL for utilization of β1,3-1,4-glucans.